2012
DOI: 10.1021/jp300531y
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Swelling Properties of Ca and Na Montmorillonite: (In Situ) Observations with Cryo-TEM and SAXS

Abstract: Aqueous dispersions of pure sodium and calcium smectite clays with platelet sizes on the order of a few hundred nanometers were characterized using a combination of cryotransmission electron microscopy (cryo-TEM) and small-angle X-ray scattering (SAXS). With monovalent sodium counterions the clay is dispersed as individual platelets, as seen by cryo-TEM, that order into a nematic phase. From SAXS a onedimensional swelling of the clay in water is observed with the characteristic spacing h s = δ/ϕ c , where h s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 50 publications
6
62
0
Order By: Relevance
“…This intensification indicated that the hydroxyl groups interacted with the organic molecules during functionalization, probably via hydrogen bonding with the organic cations. 24 The bands at 2925, 2845, and 1474 cm −1 , attributed to CH antisymmetric and symmetric vibrations of the CH 2 species present in the functionalized materials, confirmed that APTS and CTAB functionalized the clay. These bands were more intense in the Because saponite is very sensitive to acidic media, octahedral Mg 2+ may have dissolved in the reaction medium, but this phenomenon did not seem to occur herein.…”
Section: ■ Results and Discussionmentioning
confidence: 66%
“…This intensification indicated that the hydroxyl groups interacted with the organic molecules during functionalization, probably via hydrogen bonding with the organic cations. 24 The bands at 2925, 2845, and 1474 cm −1 , attributed to CH antisymmetric and symmetric vibrations of the CH 2 species present in the functionalized materials, confirmed that APTS and CTAB functionalized the clay. These bands were more intense in the Because saponite is very sensitive to acidic media, octahedral Mg 2+ may have dissolved in the reaction medium, but this phenomenon did not seem to occur herein.…”
Section: ■ Results and Discussionmentioning
confidence: 66%
“…The hierarchical morphology of the clays comprising the interlayer nanopores between adjacent clay sheets, mesopores between stacked clay sheets, 48 and larger macropores between clay grains, correspond to identifiable q -ranges in the combined USAXS/SAXS regime as presented in Figure 1. This is useful for reference in interpreting the USAXS/SAXS data in terms of the microstructural and structural changes in Na- and Ca-montmorillonite on heating, considered in detail in the following sections.…”
Section: Resultsmentioning
confidence: 99%
“…In the present case, for much of the temperature range of interest (30 °C to 1000 °C), all scattering features were assumed to be oblate pores or voids with an aspect ratio of 0.2, which is consistent with the platelet-like morphology of clays based on TEM investigations. 48 The scattering is assumed to arise from voids because the samples comprise pressed powdered clay pellets that are solid clay material except for the various hierarchical pore morphologies. The calibrated scattering intensity from the i th pore population, I i ( q ), normalized to the incident X-ray flux and sample volume, is proportional to its overall volume fraction normalized to the total sample volume, Φ Vi , and the mean volume of its individual pores, V Pi (at low and intermediate q ), to its surface area per unit sample volume, S Vi (at high q ), and to the scattering contrast factor, |Δ ρ | 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For montmorillonites dominated by small, monovalent cations the swelling in low ionic strength solutions can be sufficient to effectively form a colloidal sol (Laird, 2006;Segad et al, 2010Segad et al, , 2012a but for montmorillonite dominated by multivalent cations the swelling is restricted to a maximum mean interlayer space on the order of a nanometer (Norrish, 1954;Kjellander et al, 1988a,b;Segad et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%